Cutaneous reactions to COVID‐19 vaccine at the dermatology primary care - Martina Burlando; Astrid Herzum; Claudia Micalizzi; Emanuele Cozzani; Aurora Parodi (Immunity, Inflammation and Disease)
Abstract Introduction Coronavirus disease 2019 (COVID‐19) vaccines can cause adverse reactions, mainly from vaccine‐induced immune responses. Some of these may also involve the skin and worry unaware patients. A better understanding of such adverse reactions may reduce concerns and help promote the vaccination of large population groups. Methods All the reports of patients admitted to our Dermatology Primary Care, from March 2021 to June 2021, were retrospectively examined to collect descriptive data on skin reactions arising after COVID‐19 vaccination. Results Out of 200 vaccinated patients admitted to the Dermatology Primary Care, 21 (10.5%) referred cutaneous reactions with onset after vaccination. Only one patient required hospitalization for generalized bullous erythema multiforme, which occurred 48 h after the second vaccine dose. The other patients' cutaneous reactions to vaccination were of mild/moderate degree. Three patients presented exacerbation of their cutaneous diseases. Conclusions Cutaneous reactions observed in our sample were mostly mild or moderate. Awareness must be raised to recognize and treat eventual severe reactions. Future studies are needed to assess the incidence of cutaneous reactions following COVID‐19 vaccination.